Sensitization of TRPV1 by EP1 and IP reveals peripheral nociceptive mechanism of prostaglandins - Segi Eri; Iida Tohko; Togashi Kazuya; Higashi Tomohiro; Moriyama Tomoko; Sugimoto Yukihiko; Tominaga Tomoko; Narumiya Shuh; Tominaga Makoto (SAGE Publishing, 2005)
Abstract Prostaglandin E2 (PGE2) and prostaglandin I2 (PGI2) are major inflammatory mediators that play important roles in pain sensation and hyperalgesia. The role of their receptors (EP and IP, respectively) in inflammation has been well documented, although the EP receptor subtypes involved in this process and the underlying cellular mechanisms remain to be elucidated. The capsaicin receptor TRPV1 is a nonselective cation channel expressed in sensory neurons and activated by various noxious stimuli. TRPV1 has been reported to be critical for inflammatory pain mediated through PKA- and PKC-dependent pathways. PGE2 or PGI2increased or sensitized TRPV1 responses through EP1 or IP receptors, respectively predominantly in a PKC-dependent manner in both HEK293 cells expressing TRPV1 and mouse DRG neurons. In the presence of PGE2 or PGI2, the temperature threshold for TRPV1 activation was reduced below 35°C, so that temperatures near body temperature are sufficient to activate TRPV1. A PKA-dependent pathway was also involved in the potentiation of TRPV1 through EP4 and IP receptors upon exposure to PGE2 and PGI2, respectively. Both PGE2-induced thermal hyperalgesia and inflammatory nociceptive responses were diminished in TRPV1-deficient mice and EP1-deficient mice. IP receptor involvement was also demonstrated using TRPV1-deficient mice and IP-deficient mice. Thus, the potentiation or sensitization of TRPV1 activity through EP1 or IP activation might be one important mechanism underlying the peripheral nociceptive actions of PGE2 or PGI2.